Turkey’s Response to the Syrian Refugee Crisis and the Road Ahead - World Bank Group (World Bank, Washington, DC, 2016)
Turkey now hosts the largest refugee population in the world. The Government of Turkey (GoT) estimates the total number of registered Syrians under Temporary Protection (SuTPs) at 2,225,147. The objective of this policy brief is to collate existing publically available material on the situation of SuTPs in Turkey and to summarize: (i) the strategy and principles of Turkey’s unique response to its displacement crisis; (ii) the challenges in managing the socioeconomic dimensions of displacement; and (iii) remaining critical policy issues and the road ahead for Turkey, as well as implications for other countries’ refugee response efforts.